2015
DOI: 10.5897/ajb2014.13992
|View full text |Cite
|
Sign up to set email alerts
|

Application of zein antimicrobial edible film incorporating Zataria multiflora boiss essential oil for preservation of Iranian ultrafiltered Feta cheese

Abstract: Zein based edible film was developed and incorporated with Zataria multiflora boiss essential oil. Mechanical and microbiological characteristics of this biofilms were measured. Increasing concentration of antimicrobial agent in film reduced stretchability, tensile strength and elongation, however increased the thickness and water vapor transmission parameters (P<0.05). Addition of Z. multiflora boiss essential oil, resulted in decreasing the count of viable Salmonella enteritidis, Listeria monocytogenes, Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Zein offers advantages as a raw material in the production of biomaterials, coatings and plastic applications as it is biodegradable and renewable [2][3][4] . It has been used to develop functional biodegradable packaging [5] , packages with antimicrobial agents [6][7][8][9] , packaging for periodontal biomaterials and substrates for cell culture [10] . Studies with zein have been carried out in respect to the regeneration of osseous tissues [11] , with nanoparticles used to improve the mechanical properties of films [12,13] and edible film to increase the shelf life of pears [14] and macadamia [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Zein offers advantages as a raw material in the production of biomaterials, coatings and plastic applications as it is biodegradable and renewable [2][3][4] . It has been used to develop functional biodegradable packaging [5] , packages with antimicrobial agents [6][7][8][9] , packaging for periodontal biomaterials and substrates for cell culture [10] . Studies with zein have been carried out in respect to the regeneration of osseous tissues [11] , with nanoparticles used to improve the mechanical properties of films [12,13] and edible film to increase the shelf life of pears [14] and macadamia [15] .…”
Section: Introductionmentioning
confidence: 99%
“…According to another study, the antimicrobial film of plant essential oil increased the shelf life of bread (Lotfinia et al., 2018). Ghasemi, Javadi, Moradi, and Khosravi‐Darani (2015) were able to improve the shelf life of cheese up to 70 days by an active film containing essential oil of Zataria multiflora . In our experiment, the antibacterial active packaging used for preserving milk extended the shelf life up to 35 days.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory zone for the concentration up to 15% was found to be 138.87 ± 12.35 mm 2 for E. coli, whereas 157.42 ± 10.95 mm 2 for S. aureus 150 70 days of storage. 167 In a different investigation L. monocytogenes, E. coli, S. enteritidis, and S. aureus, strains associated with contamination of food were picked to assess the antibacterial characteristics. The outcome demonstrated that all of the tested microorganisms were inhibited by adding oil to the zein films.…”
Section: Chitosan Biocomposite Reported Effectmentioning
confidence: 99%
“…There are many studies on the utilization of maize zein as for antibacterial preformed films and consumables. To prevent microbiological spoiling of Feta cheese, Zataria multiflora boiss essential oil was infused into the films of protein by Ghasemi et al This biopreservative ingredient was added to films of corn zein to prevent the growth of L. monocytogenes , E. coli , S. aureus , and S. enteritidis , as well as to lengthen the span of time of cheese for 70 days of storage 167 . In a different investigation L. monocytogenes , E. coli , S. enteritidis , and S. aureus , strains associated with contamination of food were picked to assess the antibacterial characteristics.…”
Section: Biopolymers and Nanoparticle‐biopolymer Composites In Food P...mentioning
confidence: 99%